STROKE (ACUTE CEREBRAL CIRCULATORY DISORDER) INSULT (International journal of medical sciences, 2026)
Stroke is an acute cerebrovascular disorder resulting from ischemic or hemorrhagic damage to brain tissue and is characterized by high mortality and disability rates. According to the World Health Organization, stroke is the second leading cause of death after cardiovascular diseases. The aim of this article is to analyze the etiopathogenesis, risk factors, clinical manifestations, and modern diagnostic and therapeutic principles of stroke based on scientific literature. The study material includes leading textbooks in neurology and cardiology, as well as evidence-based clinical protocols and World Health Organization recommendations. The results indicate that early diagnosis of stroke (using CT and MRI), timely thrombolytic therapy, and stepwise rehabilitation significantly improve patient prognosis. In conclusion, effective prevention focusing on controlling arterial hypertension, atherosclerosis, diabetes, and cardiac arrhythmias is crucial in reducing stroke incidence.